VOLUNTARY AUDITOR SWETCHING: PERGANTIAN MANAJEMEN, UKURAN KANTOR AKUNTAN PUBLIK, DAN PERUBAHAN PROSENTASE ROA - Inneke Nur Vivi; Evi Dwi Kartikasari; Irma Indira (Owner : Riset dan Jurnal Akuntansi, 2023)
The size of the auditor is also one of the benchmarks of external parties to trust the results of audit opinions. Management within the company's structure is not always the same, there is a change of management that requires the company to create a new management policy, in this case, it is commonly related to the selection of KAP for external auditors. The company’s financial condition becomes the main factor that is highlighted by an auditor in providing audit opinions. Changes in the percentage of ups and downs in financial performance are also important to note by the management of the company so that the audit opinion is good. Previous research conducted by several researchers states that the change of management, the size of public accounting firms, and changes in the percentage of ROA against Auditor Switching there are positive influences and some have negative influences. This type of research is descriptive research with a quantitative approach. The population is 144 companies. A sample of 20 companies, so the sample is 120 data. Sampling method using nonprobability sampling type Purposive sampling. The results of this study are expected to be used by external and internal parties of the company to determine strategies for conducting auditor switching. The difference between this research and previous research is that the researchers conducted research on different years and objects and on different ROA conditions